A Unique Study of Sufi Rituals at the shrines of Sufi saints of Pakistan - Dr. Ali Murad Lajwan; Dr. Aijaz Ali Khoso (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
In the global era, Pakistan is a famous country owing to the land of Sufi saints. The people in this country firmly believe in mysticism, particularly women are more attached to the sacred rituals and places in Pakistan. The history of Sufi shrines narrates as Muslim era of mysticism is associated with the different Sufi orders of the 12th century in (sub-continent) Pakistan. Such the orders like Owasi, Chishti, Suharwardy, Qadri, Naqshbandi, Firdausi and so forth have been so connecting and involving people to mutually take part in the rituals. Women and men are in the equal ratio as visitors to such the shrines. The culture prevailing at Sufi shrines teach individuals the language of human love, religious harmony; tolerance and fore bearing. People often visit the different shrines for spiritual needs located at various cities and towns and pay homages to such the saints. Such the Sufi saints since the inception taught people a lesson of simplicity and goodness, and respect for other religions of the World. The first teaching journey starts to avoid being rigid and intolerant. In present research paper, the contents of Sufi rituals i.e. poetries, stories, rituals, and music have been explored. There has been the particular focus on qualitative research methods. The observation technique was implemented too! During the performance of Sufi rituals at different Sufi shrines on various special occasions. The Sufi practices are instinctively planting the seed of human love in the heart of every woman and man regardless of the gender, religious, and social difference. It equally encourages every one of us to respect the other religions and adapting the broad-mindedness. It creates an environment of exploring contents of comparative studies of different religions. The Sufi shrines are focal points to spiritual customs for all religions alike whether Muslims, Hindus, Christians or etc. Thus Sufi rituals at Sufi shrines promote social harmony, brotherhood, and tolerance